Institutionalization of Ethical Principles to Overcome Ethical Dilemmas in the Public Sector - I Made Krisnajaya (Indonesian Association for Public Administration, 2018)
Discussions on public sector ethics essentially cover three main issues. First, how to establish a theoretical argument capable of providing answers to queries about what is considered an ethical and unethical conducts in public sector management. Second, how to develop ethical instruments and standards capable of helping resolve ethical dilemmas that commonly occur in the public sector. Third, how to institutionalize ethical principles and instruments developed in public institutions. Both theoretical studies and empirical experiences indicate that the essence of the various forms of a dilemma in the public sector is the conflict between personal virtue and public virtue. These ethical dilemmas may be subdued by institutionalizing ethical principles in public institutions, and it basically involves two substantial activities, namely integration, and revitalization of ethical principles in public institutions. These ethical principles should be integrated within a system of conducts covering standard values and norms that serve as a reference in conducting oneself and in minimizing unethical conducts and in preventing maladministration in public sector management. Legal instruments remain necessary in order to ensure the effectiveness of ethical principles as a code of conduct for government personnel to carry out their tasks and functions. Of no less importance is the effort to improve leadership that highly reveres ethical principles in the public bureaucracy.